Polyphony & Complexity - Mahnkopf, Claus-Steffen; Cox, Frank; Schurig, Wolfram (Hofheim Wolke, 2002)
The appearance of a complex music undoubtedly represents one of the most significant developments in new music since the 1980's. Several commentators have considered this music as marking the advent of Second Modernity and/or a deconstructive turn in recent musical history. Given the shortage until now of detailed and serious discussions of this music, the time is certainly ripe for an interim report, one which is internationally oriented, attempts to present aestetic and compositional/technical explanations of this phenomenon, and allows the composers themselves to speak. Polyphony & Complexity by no means treats complexity as an issue limited to new music, but rather attempts to connect this issue with the central aspects of Western Music: with polyphony and the cluster of problems which it presents. The contributions treat manifold compositional and aesthetic questions such as the following: morphology, deconstruction, live-electronics, extended performance techniques, work-conception, material, multi-dimensional rhythms, and fragmentation.This volume consists of two main division, the first theoretical and the second more oriented to practical issues faced by the composers. The theoretical part includes an analysis of one of the classics of complex music, Elliott Carter's Concerto for Orchestra, a clarification of the concept and phenomenon of complex music, a theory pf polyphony, and a contribution to the performance practice of complex music. The second part incudes persentations by younger composers from Germany, the U.S.A., Switzerland, France, Italy, Gerat Britain, and Austria. The contributors to this volume are the following: Mark André, Bernd Asmus, Aaron Cassidy, Frank Cox, Gerald Eckert, James Erber, Walter Feldmann, Mario Garuti, Wieland Hoban, Klaus K. Hübler, Claus-Steffen Mahnkopf, Simeon Pironkoff, Larson Powell, Wolfram Schurig, Steven Kazuo Takasugi, Richard Toop, and Ian Willcock.
Keywords: 20th Century (1901-2000); Composing; Polyphony; Complexity